A metrópole e os mega-eventos. Implicações socioespaciais da copa do mundo de 2014 em Fortaleza - Góis, Rodolfo Anderson Damasceno (2013)
The megaevent, especially sports, is an activity that has been growing in recent years in the world, tend to generate employment, income, exposure image of the place internationally, attracting public and private resources, streamline urban projects that will enable the achievement of games and later will be a legacy of the event. In this sense, the lure of megaevents have been seen by planners, governments (those with a position of entrepreneur) and private initiative as a strategy for the growing economy, catalyst improvements and social inclusion of the city in the globalized economy. The research On the mega metropolis. Socio-spatial implications of the 2014 World Cup in Fortaleza therefore has the general objective to understand the socio-spatial implications of projects and investments in infrastructure and equipment in Fortaleza associated with this sporting event. Government structures were created in the federal, state and local in order to facilitate the completion of the World Cup 2014. In Ceará have as an example the Secretaria Especial da Copa - SECOPA conveyed to the state government and responsible for articulating the actions of other government agencies. The projects related to the mega promote profound changes in the spatial production of Fortaleza. Greater magnitude of the works of urban mobility improvements that involve pathways, Veículo Leve Sobre Trilhos - VLT and Bus Rapid Trasit - BRT stand out in the context of the mega event in Fortaleza. In the wake of these changes come into play two more agents: real estate, taking the opportunity to launch their products near the areas benefited by the works of Cup, Populations and Communities Rail calls in the vicinity of the railway project VLT fighting the removals and violations of their rights. Based on this scenario that consolidates the research seeks to understand how projects relate Cup Fortaleza urban planning and possible territorial disputes generated by singularities, the behavior of the housing market works before the mega event and compared with areas of targets removals and replacements possible use. The table is raising changes in the spatial configuration of Fortaleza